Chile - Financial Sector Assessment Program : Climate Risks and Finance - Cohen, Charles; Dijkman, Miquel (World Bank, Washington, DC, 2022)
This technical note explores the consequences of climate risks for the Chilean financial sector, and the role the financial sector can play in mobilizing resources to finance Chile’s transition to a climate resilient and low carbon economy. Globally, there is increasing attention being paid to the impact of climate related and environment risks (CRER) on the financial sector. Regulators and central banks – through the Network for Greening the Financial System (NGFS) among other fora – are warning of the impact of CRER on the stability and soundness of financial sectors. These calls follow attention paid to this topic by the FSB Task Force on Climate-related Financial Disclosures (TCFD) and the G20 Sustainable Finance Working Group. There is also global recognition of the importance of financial sectors in mobilizing resources to meet the investment need coming from transitioning to a climate resilient and low carbon society as public resources and concessional finance are not sufficient. Part one will assess how the financial authorities understand and address climate risks. Part two will assess Chile’s efforts to stimulate climate finance.